Sethusamudram Shipping Canal Project : in need of divine intervention - Chandrasekaran, K., (SAGE Knowledge. Cases., 2017)
It was January 21, 2012, a cold and foggy day in Delhi. As Rajendra Pachauri stepped out of the meeting, he knew this was going to be harder than he had imagined. Three and a half years earlier, in July 2008, Dr Manmohan Singh, the Prime Minister of India, had appointed Pachauri as the head of a six-member committee to examine an alternative alignment (Alignment 4A) for the controversial Sethusamudram Shipping Canal Project (SSCP) and provide its recommendations as soon as possible.